Long-read genome sequencing resolves a de novo complex 18q12.1q21.2 triplication causing partial tetrasomy and reveals its underlying mechanism - Serena Redaelli; Viviana Tritto; Eleonora Mangano; Roberta Bordoni; Elena Sala; Nicoletta Villa; Francesca Crosti; Leda Dalprà; Luigina Spaccini; Alessandra Sirtori; Giovanni Cazzaniga; Donatella Conconi; et al. (Human Genetics, 2026)
Chromosomal triplications are rare structural variations often associated with complex phenotypes. We report the molecular characterization of a novel intrachromosomal triplication at 18q12.1q21.2 identified in a fetus with ultrasound abnormalities. Conventional karyotyping and array-CGH revealed a partial tetrasomy and a 26 Mb region of loss of homozygosity (LOH), extending from the triplication to the telomere. Long-read sequencing (LRS) identified breakpoint junctions revealing a direct-inverted-direct triplication structure. Breakpoint analysis suggested that this rearrangement arose through a U-type exchange between sister chromatids, likely mediated by microhomology-based mechanisms. This process likely generated a transient dicentric chromosome that subsequently broke during mitosis. The resulting duplicated chromosome may have been stabilized by telomere capture, consistent with the triplicated 18q12.1q21.2 region followed by the 18q21.2q23 LOH. Nine genes within the triplicated region, including SMAD2 and SMAD4 , showed high predicted sensitivity to increased dosage, possibly contributing to the clinical phenotype. This study highlights the utility of LRS in defining complex chromosomal rearrangements and emphasizes the importance of molecular breakpoint analysis for understanding pathogenic mechanisms and improving genetic prenatal diagnosis.